Effect of relay changeover position on skating speed for elite short track speed skaters - Osborough, C.; Henderson, S. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Relay changeovers in short track speed skating take place when the incoming skater pushes the outgoing skater at the start of the straight. Time can be gained or lost during these changeovers, depending on how effectively they are executed. The position on the track where initial contact between skaters is made is thought to be a critical factor in an effective relay changeover (Riewald et al., 1997). The aim of this study was to determine how the position of the relay changeover on the track would affect skating speed (SS).